Determinants of Credit Risk: Empirical Evidence from Asia-Pacific Banking Industry - Shi, Weihan (2013)
This thesis carries out an empirical analysis of the determinants of credit risk based on Asia-Pacific banks. It has been debated for a number of years that the banks in that region are healthier than those in the US and the Europe. Presently, there are many papers available on the topic of credit risk determinants, but only a limited number of them focus on Asia-Pacific banks. Furthermore, these papers are generally based on some particular Asia-Pacific countries and none of these papers successfully identify the impact of the recent financial crisis to the whole region. Motivated by this, the author conducts a brief introduction and presents some background information on the Asia-Pacific history and the banking industry, followed by a review of the recent literature. While discovering gaps between previous studies, the author proposes three stages of the research, and carries out an empirical analysis. The first stage of the research contains only bank-level and macroeconomic variables. The author finds that loan quality, management efficiency, and bank size are significant at the bank level, and country‟s unemployment rate and inflation rate are significant at the macroeconomic level. To examine the contrasting views on the impact of financial crisis in Asia-Pacific banking industry, this thesis gives a further analysis and concludes that the recent economic downturn has no significant impact to banks in that region. The author also takes an additional research with a group of country dummy variables, and it turns out that only Philippines and Pakistan are subjective to the non-performing loans. Based on this result, the author concludes that banks in these two countries are more exposed to credit risk than any other Asia-Pacific countries.